Environmental state and buffering properties of underground hydrosphere in waste landfill site of the largest petrochemical companies in Europe; IOP Conference Series: Earth and Environmental Science; Vol. 33 : Contemporary Issues of Hydrogeology, Engineering Geology and Hydrogeoecology in Eurasia - Musin R. Kh.; Kurlyanov N. A.; Kalkamanova Z. G.; Korotchenko T. V. Tatiana Valerievna (Geoecology, 2016)
Title screen